Bridging the digital divide: Understanding COVID-19 diagnostic and vaccination experiences in a socioeconomically disadvantaged neighborhood in Sweden - Rathi Ramji; Dipak Surie; Stefan Cirovic; Margareta Rämgård; Sergey Shleev; Anders Kottorp (BMC Health Services Research)
Abstract Background The COVID-19 pandemic had a significant impact on the public health and the economy of the Swedish population, with disproportionate effects on communities living in socioeconomically diverse neighborhoods. To mitigate these impacts and enhance outreach, COVID-19 diagnostic and prevention services supported by digital health tools were introduced for early diagnosis and prevention. Assessing the perceptions related to utilization of these efforts is essential to ensure they are benefiting the particular populations living in socioeconomically disadvantaged neighborhoods. Therefore, the aim of this study was to demonstrate available COVID-19 diagnostic tools and explore the implementation of COVID-19 diagnostics and the digital support services from the experiences of lay health promoters (LHPs) in a socioeconomically disadvantaged neighborhood in Malmö. Method Five LHPs participated in an online focus group via Zoom, in May 2021. The session began with an online presentation of testing procedures, followed by discussion to gather user perspectives. The data was analyzed using the Rapid Identification of Themes from Audio recordings method. Results Health promoters reported a lack of trust in existing COVID self-test procedures due to validity issues and frequent false-negative results. Polymerase chain reaction testing procedures were deemed inadequate because of delays in receiving results. Additionally, the neighborhood faced barriers to vaccination access, including challenges in using digital technology to book test and vaccination, distance to vaccination centers, and unavailability of slots. Conclusion This study highlights the need for affordable and easy-to-use COVID-19 test alternatives in these neighborhoods. The implementation of digital healthcare solutions during the pandemic faced significant challenges, limiting access to care and support in socioeconomically disadvantaged neighborhoods. Therefore, implementing digital healthcare initiatives for disease diagnosis and prevention at the national level requires strategic planning that considers the needs and capabilities of residents in socioeconomically disadvantaged areas. Furthermore, the importance of increasing targeted vaccination centers and educating community representatives, such as health promoters, to better support their communities during crises, was emphasized.